2018
DOI: 10.5539/jel.v7n5p156
|View full text |Cite
|
Sign up to set email alerts
|

In-Service Mathematics Teachers’ Beliefs About Teaching, Learning and Nature of Mathematics and Their Mathematics Teaching Practices

Abstract: The aim of this study is four fold: (a) to investigate the beliefs of elementary (grades 1-3) and middle school (4-6 grades) math teachers about teaching, learning and nature of mathematics; (b) to explore their teaching practices of mathematics; (c) to study the impact of their educational qualifications, years of experience, major on their beliefs toward teaching, learning and nature of mathematics, and; (d) to explore the relationship between their beliefs about teaching learning and nature of mathematics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In order to achieve the objective of DSKP, which is to produce students that who are enhanced in mathematical thinking, the mathematical thinking abilities of teachers also need to be taken seriously. This is due to it being possible that educator's attitudes toward mathematical thinking shows the complicated connection between their knowledge and their effectiveness as educators (Aljaberi & Gheith, 2018). If a teacher always performs a negative belief toward mathematical thinking, the quality of the teaching and learning session will be affected and decline.…”
Section: Universiti Pendidikan Sultan Idris Perak Malaysiamentioning
confidence: 99%
“…In order to achieve the objective of DSKP, which is to produce students that who are enhanced in mathematical thinking, the mathematical thinking abilities of teachers also need to be taken seriously. This is due to it being possible that educator's attitudes toward mathematical thinking shows the complicated connection between their knowledge and their effectiveness as educators (Aljaberi & Gheith, 2018). If a teacher always performs a negative belief toward mathematical thinking, the quality of the teaching and learning session will be affected and decline.…”
Section: Universiti Pendidikan Sultan Idris Perak Malaysiamentioning
confidence: 99%
“…In other words, teaching practices were determined using their perceptions. For instance, a study conducted by Aljaberi and Gheith (2018) examined mathematics teachers' teaching practices through survey items in terms of their preferred approach to teaching mathematics in the classroom. They concluded that the perceptions of the teachers were mainly inclined toward the constructivist approach.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Several researches in mathematics education have paid more attention to teachers' beliefs about mathematics to find accepted explanations and to expect teachers' teaching practices. They addressed teachers' beliefs to illustrate the complex relationship between teachers' knowledge and their educational effectiveness (Aljaberi & Gheith, 2018;Haciomeroglu, 2013;Philipp, 2007). Beliefs were described as a complex construction which can influence the decisions of the teacher and also affect on their professional development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some another researches divided mathematical beliefs about mathematics learning, beliefs about mathematics teaching and beliefs about the effectiveness of learning and teaching mathematics. While, some other researches defined beliefs about mathematics nature and mathematics assessment as dimensions of beliefs about mathematics (Aljaberi & Gheith, 2018;Memnun & Katranci, 2012;Purnomo, 2017).…”
Section: Measuring Teachers' Beliefs About Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation